127=6x-13

Simple and best practice solution for 127=6x-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 127=6x-13 equation:



127=6x-13
We move all terms to the left:
127-(6x-13)=0
We get rid of parentheses
-6x+13+127=0
We add all the numbers together, and all the variables
-6x+140=0
We move all terms containing x to the left, all other terms to the right
-6x=-140
x=-140/-6
x=23+1/3

See similar equations:

| 3�−39=3b−39=  −78−78 | | 50-q=5+q | | -9(-v-10)=10-v | | 1.07*x=3500 | | 13=-2/3x-7 | | 3(x-7)=12x | | 60.536=9.2j= | | F(x)=-49+3.6x-0.04x2 | | -8(y-1.24)=4 | | q+–9=–3 | | 6x+8=-1+6x+12 | | –18=–2r | | 7x+11=3x+19 | | 5x³+4x²-57x=0 | | 3^(x-2)=99 | | 7x+2=1/7x-5 | | 0.2x+1=2 | | 74=7x+1 | | 74=7x+1 | | 97=9x+11 | | 97=9x+11 | | 51=7x+16 | | 6-z1=24 | | F(11)=3(2x+7) | | F(11)=3(2x+7) | | F(11)=3(2x+7) | | 2(j-3)+2.65=7.65 | | 2(j-3)+2.65=7.65 | | 2(j-3)+2.65=7.65 | | 2(j-3)+2.65=7.65 | | 2(j-3)+2.65=7.65 | | 16n+(-18)n=14 |

Equations solver categories